N-glycosylation enhances presentation of an MHC class I restricted epitope from tyrosinase - Ostankovitch, Marina (2009)
We recently demonstrated that the mechanism of processing of an HLA-A*0201-restricted peptide epitope, Tyr(369)(D), derived from the membrane protein tyrosinase, involves retrotranslocation of glycosylated molecules from the endoplasmic reticulum to the cytosol; removal of an N-linked carbohydrate from Asn371 by peptide N-glycanase; proteolysis by the proteasome and other proteases; and retransport of the resulting peptides into the endoplasmic reticulum for association with HLA-A*0201. Carbohydrate removal results in deamidation of Asn371 to Asp. The Asn-containing homolog of this peptide, Tyr(369)(N), is not presented by tyrosinase-expressing cells, and this has been presumed to be due to quantitative glycosylation of Asn371. While examining cytosolic intermediates that accumulated in human melanoma cells treated with proteasome inhibitors, we were surprised to find both molecules that had been deglycosylated by peptide N-glycanase and a large number of molecules that had not been previously glycosylated. The failure of Tyr(369)(N) to be processed and presented from these latter molecules may be partially due to a process of deamidation independent of glycosylation. However, we also established that proteasomes degrade tyrosinase molecules that are still glycosylated, giving rise to a set of discrete intermediates that are not observed when unglycosylated molecules are degraded. We propose that Tyr(369)(N) fails to be presented because unglycosylated tyrosinase is degraded rapidly and relatively non-selectively. In contrast, glycosylation alters the selectivity of tyrosinase processing by the proteasome, enhancing the production or survival of Tyr(369)(D).